Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Keputusan Pembelian Motor Honda pada Wahana Honda Ciracas - Gabriela Patricia; Elmira Siska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of information technology has driven a significant transformation in business strategy, including in the automotive industry. This study aims to analyze the influence of digital marketing and service quality on the purchase decision of Honda motorcycles on the Honda Ciracas Ride. The shift from conventional to digital marketing and the high competition of the automotive industry in the East Jakarta area are important backgrounds for this study. The research method used is a quantitative approach with survey techniques through questionnaires distributed to 263 respondents who have made purchases. Data analysis was carried out using SPSS software with a series of statistical tests, including validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study showed that partially, digital marketing had a positive and significant effect on purchase decisions, with a t-count value of 2.355 > t-table of 1.970 and a significance of 0.019 < 0.05. The quality of service also showed a positive and significant influence, with a t-count value of 7.782 > t-table of 1.970 and a significance of 0.000 < 0.05. Simultaneously, these two variables have a significant effect on purchasing decisions, shown by the F-calculation value of 66.438 > F-table 3.030 and the significance of 0.000 < 0.05. These findings confirm the importance of optimizing digital marketing strategies and improving service quality in improving consumer purchasing decisions in the automotive sector.